Syntheses of spliceostatins and thailanstatins: a review - Donaldson, William A. (Beilstein Journal of Organic Chemistry, 2020)
The spliceostatins/thailanstatins are a family of linear peptides/polyketides that inhibit pre-mRNA splicing, and as such act as potent cytotoxic compounds. These compounds generally contain 9 stereocenters spread over a common (2Z,4S)-4-acetoxy-2-butenamide fragment, an (all-cis)-2,3,5,6-tetrasubstituted tetrahydropyran fragment and a terminal oxane ring joined by a dienyl chain. Due to the impressive antitumor properties of these compounds, along with their complex structure, a number of total syntheses have been reported. This review will compare the synthetic strategies reported through the end of 2019.
Keywords: antiproliferative; polyketide natural products; tetrahydropyrans; total synthesis